Optimalisasi Pasar Keripik Pisang Melalui Re-Branding untuk Mengembangkan Bisnis “Keripik Pisang NEVY” - Halim*, Jodi; Nurhaliza, Hanum; Belinda, Leoni; Sivali, Jonathan; Roja, Haekal; Geraldine, Alyssa; Stephenson, Jordan; Akbar, Teuku Fajar (Pusat Pengabdian kepada Masyarakat (PPKM) Universitas Prasetiya Mulya, 2019)
Rebranding is the way used by companies for developing, from the small size upto sustain company. We do this research to know how to optimize banana chips market belongs to NEVY’s banana chips business. The result of this research is using for exploration purpose that is finding newknowledge, and to be reference for college student to developing a business especially in Cianjur. In branding we use a few words such as brand brand identity, brand image, brand personality, brand positioning, brand element, that stand for this rebranding process. A lot of steps which is conducted to do this method, the most seen factor are the transformation of brand element that starts from name, logo, and packaging. Social media is also an important thing to do pasaring to reach wider audience. According to this research, the result is rebranding fitted the most to do, because there is fundamental transformation. Starts from target market, brand personality,and sales. This analysis gave a good result such as increasing sales until 200% from recent sales. The way we sell is not only by preorder but from organic selling as well.